AAA+ ATPases: structural insertions under the magnifying glass. (February 2021) - Jessop, Matthew; Felix, Jan; Gutsche, Irina
Graphical abstract: Highlights: Cryo-EM has enabled rapid advances in understanding of AAA+ ATPases. Functions of AAA+ proteins are fine-tuned by insertions in the conserved AAA+ core. Structural analysis reveals inconsistencies in AAA+ ATPase classification. The existence of a unifying ATPase mechanism for all AAA+ proteins is still debated. Abstract : AAA+ ATPases are a diverse protein superfamily which power a vast number of cellular processes, from protein degradation to genome replication and ribosome biogenesis. The latest advances in cryo-EM have resulted in a spectacular increase in the number and quality of AAA+ ATPase structures. This abundance of new information enables closer examination of different types of structural insertions into the conserved core, revealing discrepancies in the current classification of AAA+ modules into clades. Additionally, combined with biochemical data, it has allowed rapid progress in our understanding of structure-functional relationships and provided arguments both in favour and against the existence of a unifying molecular mechanism for the ATPase activity and action on substrates, stimulating further intensive research.